Preparation and Characteristic Study of Pure and Na2O Doped NiO-Mn2O3-MgO Catalyst - Nasser Hussein, Najlaa; Hadi Kadhim, Salih (Al-Qadisiyah Journal of Pure Science, 2018)
The catalyst NiO-Mn2O3-MgO was prepared in the ratio of 10:50:40 for the mixed oxides respectively, by using the coprecipitation method of their mixed bicarbonates ,from their nitrates solution using 1M NaHCO3 solution at constant pH ,dried at 100°C and calcinated at different temperatures (400,500,600,700 and 800) °C for 4 hours . The Na2O doped mixed oxide were prepared by impregnating a given dry weight of Ni,Mn and Mg basic bicarbonate M (HCO3)2 with a solution containing different amounts of sodium nitrate (2%,4%,6% and 8%) sufficient to make paste. The paste were dried at 110°C and then calcined at 600°C for 4 hrs . surface and catalytic properties of the pure and Na2O doped catalyst were investigated using XRD, atomic absorption spectrophotometer, UV-visible techniques and wet impregnation method. The degree of crystallinity and crystallite size of the produced phase increased progressively as a function of calcination temperature from (400 to 600)°C,but decreased at (700 and 800) °C .The catalytic activity of pure and doped catalyst was tested in the degradation of reactive red dye in the presence of ultraviolet light ,and study the effect of temperature on the activity of catalyst. The results showed that the doped catalyst has a smaller activation energy(13 kJmol.-1 ) than the pure catalyst(17.8 kJmol.-1 ) .